Identification, Selection, and Response of Radiation Induced Towuti Mutant Rice (Oryza Sativa L.) in Drought Stress Conditions - H. Dama; S. I. Aisyah; S Sudarsono; A. K. Dewi; K. Wibisono (Atom Indonesia, 2022)
Climate change with the impact of drought stress has become a major environmental problem for rice (Oryza sativa L.). The use of gamma ray radiation at a dose of 300 Gy is one way to develop drought tolerant rice varieties with little change to the characteristics of the Towuti variety. However, research is still needed to determine its resistance to drought stress. This study aims to identify characters for selection, genotype selection, and determine the response of Towuti mutant rice to drought stress conditions.The characters that can be used to select rice genotypes under drought stress conditions are plant height, number of leaves, number of tillers, and SPAD chlorophyll value. The Towuti mutant has the best tolerance to drought stress compared to other genotypes. Tolerance to drought stress in the Towuti mutant is not caused by the stay-green gene.